Determinants of foreign direct investment: empirical evidence from Southern Africa Customs Union (SACU) countries - Suleiman, Najat Nassor; Kaliappan, Shivee Ranjanee; Ismail, Normaz Wana (Faculty of Economics and Management, Universiti Putra Malaysia, 2015)
This study examines the determinants of Foreign Direct Investment (FDI) in southern Africa Custom union (SACU) countries. The study employed panel data from the period 1990–2010 and used pooled OLS as the main estimation method. The findings reveal that market size, natural resource availability and trade openness are positive and significant determinants of FDI for the SACU member countries. Therefore, these countries should undertake more agreements in trade partnership and should reform investment policy to attract more foreign inflow into SACU countries in the long run.